Predictors of early renal function decline in adults with Type 1 diabetes: the Coronary Artery Calcification in Type 1 Diabetes and the Pittsburgh Epidemiology of Diabetes Complications studies. Issue 11 (14th August 2017) - Bjornstad, P.; Costacou, T.; Miller, R. G.; Maahs, D. M.; Rewers, M. J.; Orchard, T. J.; Snell‐Bergeon, J. K.
Abstract: Aim: Diabetic kidney disease is one of the leading complications of Type 1 diabetes, but its prediction remains a challenge. We examined predictors of rapid decline in estimated GFR (eGFR) in two Type 1 diabetes cohorts: the Coronary Artery Calcification in Type 1 Diabetes (CACTI) and the Pittsburgh Epidemiology of Diabetes Complications (EDC). Methods: A select subset of participants (CACTI: n  = 210 and EDC: n  = 98) diagnosed before 17 years of age with Type 1 diabetes duration ≥ 7 years, and follow‐up data on eGFR by CKD‐EPI creatinine for up to 8 years were included in the analyses. Early renal function decline was defined as annual decline in eGFR ≥ 3 ml/min/1.73 m 2, and normal age‐related decline as eGFR ≤ 1 ml/min/1.73 m 2 . Parallel logistic regression models were constructed in the two cohorts. Results: Early renal function decline incidence was 36% in CACTI and 41% in EDC. In both cohorts, greater baseline eGFR (CACTI: OR 3.12, 95% CI 1.97–5.05; EDC: OR 1.92, 95% CI 1.17–3.15 per 10 ml/min/1.73 m 2 ) and log albumin‐to‐creatinine (ACR) (CACTI: OR 3.24, 95% CI 1.80–5.83; EDC: OR 1.87, 95% CI 1.18–2.96 per 1 unit) predicted greater odds of early renal function decline in fully adjusted models. Conversely, ACE inhibition predicted lower odds of early renal function decline in women in CACTI, but similar relationships were not observed in women in EDC. Conclusions: A substantial proportion of people with Type 1 diabetes in the EDC and CACTI cohorts experienced early renal function decline over time. ACE inhibition appeared to be protective only in women in CACTI where the prevalence of its use was twofold higher compared with the EDC. What's new?: Early renal function decline is increasingly recognized as an intermediate phenotype of diabetic kidney disease. In this parallel analysis in the Coronary Artery Calcification in Type 1 Diabetes (CACTI) and Pittsburgh Epidemiology of Diabetes Complications (EDC) studies, baseline estimated GFR and albuminuria were the strongest predictors of early renal function decline.